Addressing buprenorphine supply barriers: A guidance commentary - Khail, Jordan W.; Rawal, Smita; Young, Henry N.; Caballero, Joshua (Journal of the American Pharmacists Association, 2024)
The current supply-side constraints limiting buprenorphine availability at pharmacies may reduce the potential impact of recent initiatives to improve medications for opioid use disorder (MOUD) access. The recent opioid litigation combined with existing federal regulation and enforcement has resulted in significant restrictions to the distribution and dispensing practices of pharmaceutical wholesalers and pharmacies countrywide. Previously discussed solutions to these problems do not seem to have produced actionable improvements to the current landscape. However, a novel solution to this problem may exist in the form of a Drug Enforcement Administration (DEA) guidance letter. These guidance letters allow the DEA to communicate directly to registrants, providing detailed interpretation and clarity regarding the DEA’s expectations and enforcement realities. Recently, the DEA guidance letter portal was used to remind registrants that the DEA does not create quantitative thresholds or volume limits on controlled substance distribution. An additional guidance letter could be issued to ease the concerns about liability connected to the distribution and dispensing of buprenorphine. In particular, this guidance could acknowledge certain terms of the distributor settlement agreement as legal precedent and clarify that buprenorphine is not subject to the same restriction as other defined “highly diverted” controlled substances. Such guidance may also serve to provide both pharmaceutical wholesalers and pharmacies with assurance that an increase in buprenorphine distribution would not directly result in increased DEA scrutiny. This strategy represents an actionable step toward the goal of providing better access to MOUD by reducing existing supply-side limitations.